Antioxidant Activity of AuPt Nanoparticle with Square-Wave Pulse Deposition Method - Syafei, Devi Indrawati (Chemistry and Materials, 2024)
Gold nanoparticles and platinum nanoparticles are considered to be effective antioxidants due to their ability in inhibiting free radicals. In this research, AuPt nanoparticles were synthesized using a square wave pulse deposition method by varying the lower potential (EL). The XRD results stated that AuPt nanoparticles had formed on the FTO substrate. The shape of AuPt nanoparticles is an irregular sphere in SEM-EDX characterization. EDX characterization also concluded that AuPt nanoparticles had formed on the FTO substrate. Antioxidant testing using the DPPH test resulted the largest inhibition value for AuPt NPs, with a lower potential of -0.6 V and the inhibition activity of 77.17%.